2015
DOI: 10.1007/s00268-015-3105-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Intravenous Lidocaine for Postoperative Analgesia Following Laparoscopic Surgery: A Meta‐Analysis

Abstract: IV lidocaine has a multidimensional effect on the quality of recovery. IV lidocaine was associated with lower opiate requirements, reduced nausea and vomiting and a shorter time until resumption of diet. Whilst IV lidocaine appears safe, the optimal treatment regimen remains unknown. Statistical heterogeneity was high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
61
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 82 publications
6
61
1
2
Order By: Relevance
“…In the current study, the incidence of nausea and vomiting were significantly lower in both gabapentin group and combination groups compared to placebo group, but no significant difference was found in lidocaine group if compared to placebo. These results were in accordance with previous studies using perioperative IV lidocaine during surgery with no effect on PONV [14] [30], while in other studies lidocaine could reduce nausea and vomiting, this may be mediated by a reduction in ileus as most of these studies were conducted in abdominal surgery [25].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In the current study, the incidence of nausea and vomiting were significantly lower in both gabapentin group and combination groups compared to placebo group, but no significant difference was found in lidocaine group if compared to placebo. These results were in accordance with previous studies using perioperative IV lidocaine during surgery with no effect on PONV [14] [30], while in other studies lidocaine could reduce nausea and vomiting, this may be mediated by a reduction in ileus as most of these studies were conducted in abdominal surgery [25].…”
Section: Discussionsupporting
confidence: 82%
“…Although both IV lidocaine infusion [13] lower VAS values and reduced postoperative analgesic consumption, but some studies and meta-analyses showed contrasting results regarding the analgesic effect of lidocaine [25] and gabapentin due to differences in used doses and used regimens or time of application [21]- [27] with the need of more researches to specify the actual value of both drugs for providing sufficient analgesia in various surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Opioid requirement is an objective surrogate for the patient pain experience [17]. In the present study, fentanyl consumption and FPB for the first 4 h following thyroidectomy were significantly decreased in the lidocaine group from that in the control group as well as correlated with postoperative pain scores.…”
Section: Discussionmentioning
confidence: 90%
“…In the recovery room and postoperatively, a continuous lidocaine infusion at a rate of approximately 1–1.5 mg/kg/hr IV for up to 48 h postoperatively has been shown to be beneficial (McEvoy et al 2016; Wongyingsinn et al 2011; Ventham et al 2015). The optimal dosing and duration of lidocaine is still not known, and the side effects are directly related to the serum lidocaine level (Khan et al 2016a)…”
Section: Postoperative-pacu To Wardmentioning
confidence: 99%
“…One study reported using a postoperative lidocaine infusion for 24 h in all CRS patients, either immediately for those who received truncal blocks or after TEA catheter removal for those receiving an epidural, which typically delineated laparoscopic versus open cases, respectively, (McEvoy et al 2016). Furthermore, a number of other studies have reported beneficial effects on length of stay, opioid consumption, nausea and vomiting, and gastrointestinal function with the use of lidocaine infusions for 24–28 h postoperatively (Wongyingsinn et al 2011; Ventham et al 2015). Additionally, an ultra-low-dose ketamine infusion (e.g., 2 mcg/kg/min) may be of benefit (Ding et al 2014; Laskowski et al 2011; Sami Mebazaa et al 2008) Maximum utilization of non-opioid medications should be used throughout the postoperative period and continued after a TEA catheter is removed and/or IV infusions are discontinued.…”
Section: Postoperative—transition From Ward To Homementioning
confidence: 99%